2023
DOI: 10.1590/0103-6440202304998
|View full text |Cite
|
Sign up to set email alerts
|

Failure behavior of zirconia crowns subjected to air abrasion with different particle sizes

Abstract: This study aimed to investigate the failure behavior of 3 mol.% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP) prosthetic crowns air-abraded with aluminum oxide (AO) particles of different sizes. Ninety ceramic premolar crowns were produced with 3Y-TZP frameworks veneered with porcelain. Crowns were randomly divided into three groups, according to the size of the air abrasion AO particles (n = 30): (GC) untreated (control); (G53) 53 µm; (G125) 125 µm. Air abrasion was performed with 0.25 mpa pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Surprisingly, the results were the opposite for the crown specimens, where the 4Y-PSZ and 5Y-PSZ specimens revealed much higher failure loads than 3Y-PSZ. Possible reasons for this discrepancy include the role of crown thickness [15,16], surface treatment [16][17][18], and cement type [38]. There are no ISO and ASTM standards for crown testing, in terms of cement type/thickness, crown thickness, or internal surface treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the results were the opposite for the crown specimens, where the 4Y-PSZ and 5Y-PSZ specimens revealed much higher failure loads than 3Y-PSZ. Possible reasons for this discrepancy include the role of crown thickness [15,16], surface treatment [16][17][18], and cement type [38]. There are no ISO and ASTM standards for crown testing, in terms of cement type/thickness, crown thickness, or internal surface treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of newer engineering materials, part of the tetragonal phase has been replaced with the cubic phase to yield yttria-partially stabilized zirconia (Y-PSZ) with a cubic phase that improves optical properties to be comparable with glass ceramic restorations [8]. The mechanical properties of zirconia restorations can be attributed to the type, and amount of stabilizing oxide [9][10][11][12][13][14][15], surface treatment [16][17][18], sintering conditions [19], ceramic thickness [15,16], zirconia phase [20,21], and translucency [22]. It has been shown that decreasing the amount of yttria strengthens zirconia [15], while increasing the yttria concentration increases its translucency [9], thus creating a trade-off between these desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Before cementation, crowns and abutments were sonically cleaned with isopropyl alcohol for 5 min. The dentin analog abutments were etched using 10% hydrofluoric acid (HF) for 60 s (Condac Porcelana, FGM, Joinville, SC, Brazil) in order to produce micro-retention for adhesive bonding, washed for 30 s, air-dried, and a silane bonding agent (Prosil, FGM, Joinville, SC, Brazil) was applied and allowed to evaporate for 60 s [ 7 , 16 , 29 ]. An adhesive system (ED Primer A + B, Kuraray, Tokyo, Japan) was applied to the dentin analog surface prior to cementation.…”
Section: Methodsmentioning
confidence: 99%
“…Resin-based cement pastes (Panavia F, Kuraray, Tokyo, Japan) were mixed and applied to the internal surface of the crown. The crown was placed over the abutment with finger pressure and assembled to a cementation device, in which a static load of 750 g was applied to the occlusal surface for 5 min (aiming to standardize the cement thickness) [ 7 , 29 ]. The excess cement was removed from the margins and light cured (1200 mW/cm 2 ) for 20 s at each surface, including the occlusal surface (Radii-cal, SDI Brasil Ind.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation